2015
DOI: 10.1093/treephys/tpv082
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the late lignification of the G-layer inSimaroubatension wood, to assist understanding how non-G-layer species produce tensile stress

Abstract: To recover verticality after disturbance, angiosperm trees produce 'tension wood' allowing them to bend actively. The driving force of the tension has been shown to take place in the G-layer, a specific unlignified layer of the cell wall observed in most temperate species. However, in tropical rain forests, the G-layer is often absent and the mechanism generating the forces to reorient trees remains unclear. A study was carried out on tilted seedlings, saplings and adult Simarouba amara Aubl. trees-a species k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 44 publications
1
40
0
Order By: Relevance
“…Simarouba amara (Simaroubaceae) is a typical example of those species [59]. By microscopic observations, Roussel and Clair observed that S. amara does produce a G-layer only at a temporary stage of cell wall development; however, it was masked by lignin deposited at a more advanced stage [59].…”
Section: Tension Wood In Magnoliaceaementioning
confidence: 99%
See 2 more Smart Citations
“…Simarouba amara (Simaroubaceae) is a typical example of those species [59]. By microscopic observations, Roussel and Clair observed that S. amara does produce a G-layer only at a temporary stage of cell wall development; however, it was masked by lignin deposited at a more advanced stage [59].…”
Section: Tension Wood In Magnoliaceaementioning
confidence: 99%
“…Ruelle et al reported that, in the tension wood of S. amara, the orientation of cellulose microfibrils is nearly parallel to the fiber axis, and its crystalline size is also significantly higher like in tension wood of Eperia falcataria, a tropical species producing a typical G-layer [60]. With reference to Ruelle et al, Roussel and Clair consider that the mechanism which generates the high tensile stress in tension wood of S. amara is likely to be the same as in species showing a typical unlignified G-layer [59]. wall.…”
Section: Tension Wood In Magnoliaceaementioning
confidence: 99%
See 1 more Smart Citation
“…TW G-layers have high cellulose content and no lignin or are later lignified during the maturation process in some species but the level of lignification has been shown to be qualitatively lower in lignified G-layers [41]. Regarding CW, complete reviews are already available [54].…”
Section: Chemical Composition Of Reaction Woodsmentioning
confidence: 99%
“…Therefore, TW is an attractive experimental system for exploring the development and the biochemical pathways of the secondary cell wall formation, as well as the mechanism underlying the induction and the formation of TW. Different stimuli are known to induce TW formation, especially the gravitational and hormonal stimuli (Jin et al 2014;Gerttula et al 2015;Gritsch et al 2015;Roussel and Clair 2015). Auxins mediate seasonal changes of cambial activity as a positional signal (Uggla et al 1996(Uggla et al , 1998 and, probably, they also play a key role in the control of TW formation (Morey and Cronshaw 1968a;Du et al 2004).…”
Section: Introductionmentioning
confidence: 99%